1997
DOI: 10.2165/00007256-199723050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Rehabilitation from Sports Injuries

Abstract: Medical professionals realise the importance of incorporating psychological strategies into rehabilitation from athletic injury, but often feel they lack the knowledge to do so. This paper explores the role which psychology can play when injured athletes are rehabilitating. Rehabilitation from sport injury involves not only physical, but psychological considerations. Topics include: the post-injury emotional and cognitive reactions of athletes, the importance of social support, the athlete's attitude toward re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 10 publications
2
52
0
6
Order By: Relevance
“…Although the participants' experiences of lessons learned have been supported in the literature, so has their tendency to report doubts about their ability to return to play. [20][21][22] Additionally, previous research [17][18][19][20][21] provides more support for the emotional response of fear of reinjury when compared with the emotion of excitement, as noted by some athletes in the current sample. The resulting behavioral response, cautiousness in their return to play, appears to be directly related to athletes' fear of reinjury.…”
Section: Discussionsupporting
confidence: 52%
“…Although the participants' experiences of lessons learned have been supported in the literature, so has their tendency to report doubts about their ability to return to play. [20][21][22] Additionally, previous research [17][18][19][20][21] provides more support for the emotional response of fear of reinjury when compared with the emotion of excitement, as noted by some athletes in the current sample. The resulting behavioral response, cautiousness in their return to play, appears to be directly related to athletes' fear of reinjury.…”
Section: Discussionsupporting
confidence: 52%
“…8 In both studies, the key strategies used with athletes were creating variety in rehabilitation exercises and short-term goal setting. In addition, SMPs are reported 2,[18][19][20][21][22] to have central roles in dealing with injured athletes' typical psychosocial responses to injuries and in influencing their overall recovery. Ideally, an athlete will have access to a range of allied health professionals during rehabilitation, including a sport psychologist 23 ; however, very rarely do athletes outside of professional sport have access to such services, 8,17,24 thereby highlighting the need for the SMP to develop competencies in the psychosocial aspects of injury rehabilitation.…”
mentioning
confidence: 99%
“…5,11,12 In addition, the role of sports medicine professionals (a situational factor) in influencing injured athletes' cognitive appraisal of the injury, emotional and behavioral responses, the rehabilitation process, and the physical and psychological recovery outcomes is also important. [13][14][15][16][17][18] Therefore, it has been suggested that sports medicine professionals, such as athletic trainers (ATs), play an integral part in the sport-injury rehabilitation process and that they are best suited to inform, educate, and assist injured athletes with the psychological and physical process of injury. 4,19,20 Indeed, many sports medicine professionals believe they must address psychological aspects of injuries in order for their work to be effective.…”
mentioning
confidence: 99%